Biosensors for single-cell analysis (Academic Press, 2022)
"Explores a range of biosensors for single-cell analysis alongside conventional and biophysical approaches to characterization ... The book is divided based on five key biophysical and chemical single-cell properties, including proteomic, metabolic, electrical, mechanical, and optical properties. Each chapter features key definitions and case studies, providing detailed guidance for research to replicate their own work, tutorial sections, evaluations of the current state of the field, and future developments. Microfluidic approaches to characterization, such as microfluidic impedance flow cytometry and microfluidic mechanical flow cytometry, are considered alongside more conventional approaches, such as mass spectroscopy and fluorescent flow cytometry. In addition, key types of biosensors are covered, including atomic force microscopy, micropipette aspiration, optical tweezers, microfluidic hydrodynamic stretchers, microfluidic constriction channel, and microfluidic optical stretchers. This book is a useful reference on the application of biosensor technology as an analytical tool for single-cell investigation, providing an overview from fundamental knowledge to practice"--Print version, page 4 of cover.